2003
DOI: 10.1118/1.1597771
|View full text |Cite
|
Sign up to set email alerts
|

Effect of saccharide additives on response of ferrous–agarose–xylenol orange radiotherapy gel dosimeters

Abstract: Glucose, sucrose, starch, and locust bean gum have been used as additives to the ferrous-agarose-xylenol orange (FAX) gel dosimeter. The saccharide enhanced dosimeters were found to have a higher dose sensitivity over a standard FAX gel as measured by both optical density change and magnetic resonance imaging (MRI). With optical density measurement, OD-dose sensitivity increases were up to 55% for glucose, 122% for sucrose and 43% for starch, while locust bean gum did not give a consistent response. With MRI, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 17 publications
1
24
0
1
Order By: Relevance
“…The standard deviation is less than 0.4% of the calculated extinction coefficient. Healy et al 15 The variations in molar extinction coefficients have been attributed to variations in impurities in the xylenol orange from different manufacturers. In this study the xylenol orange was from Acros Organic which has not been included in the reported work.…”
Section: Extinction Coefficientmentioning
confidence: 99%
“…The standard deviation is less than 0.4% of the calculated extinction coefficient. Healy et al 15 The variations in molar extinction coefficients have been attributed to variations in impurities in the xylenol orange from different manufacturers. In this study the xylenol orange was from Acros Organic which has not been included in the reported work.…”
Section: Extinction Coefficientmentioning
confidence: 99%
“…Phantoms can easily be obtained and used as dosimeter to obtain 3-D dose distribution. Different kinds of gel dosimeters have been developed, the two main investigated groups are the aqueous gels, the Fricke gel dosimeters [4,5,6,7,8,9] and the based on radiation-induced polymerization and cross-linking of acrylic monomers, the polymer gels [3,10,11,12,13]. Imaging techniques such us spectrophotometry and MRI scanning, have been proposed [14,15,16,17].…”
Section: Introductionmentioning
confidence: 99%
“…The elevated temperature has been problematic for many of the radiation chemistries that were investigated. For example, heating reduces the amount of dissolved oxygen and increases auto-oxidation rates [14]. This can lead to chemically nonuniform gels with unnecessarily elevated background levels for optical studies.…”
Section: Hydrogelsmentioning
confidence: 99%